Investigating the Rise in Pediatric Obesity Among Children Aged 1 to 5: The Impact of Nutritional Intake and Dietary Patterns (Medical Forum Monthly, 2024)
Objective: The purpose of study is to determine the effects of nutrient and dietary on the increasing prevalence of obesity amongst children of age 1 to 5 years.Study Design: A Cross Sectional StudyPlace and Duration of Study: This study was conducted at the Department of Pediatrics, HMC Peshawar, starting January 2023 to January 2024.Methods: Consequently, the sample was selected from 300 children at the age of 1 to 5 years. Dietary consumption habits were captured using the parent’s self-administered dietary forms, while the child’s BMI was determined to categorise weight status. Information were also analyzed and compared with a view to identifying relationship between eating habits and obesity.Results: The mean age of the children was 3. 2 years SD = 1. 4 years. Of the 300 participants, 28% of the participants were categorised as obese, 15% as overweight, and 57% as having normal weight. The study further showed that there was a difference in dietary behaviour between the Obese and non-Obese groups (p < 0. 05). Boy and girl and boy child consuming a large number of calories were more likely to be obese.Conclusion: The study therefore finds that unfavourable dietary practices are rapidly contributing to obesity among the 1 to 5 years old children in Peshawar. It is now important that giving proper information to parents and having healthcare providers’ cooperation to make early prevention because this ascending public health problem.